The Assessment of Resilience and Burnout in Correctional Officers - Klinoff, Vera A. (Criminal justice and behavior, 2018)
Despite the awareness of occupational stress in first responders, virtually no investigations have focused on correctional officer resilience. The purpose of this study was to (a) identify whether personal strengths (i.e., hope, optimism, social support) are associated with increased resilience, (b) determine the extent to which resilience protects against job burnout, and (c) ascertain whether resilience mediates the negative relationship between personal strengths and reduced burnout. Correctional officers (N = 300) were randomly selected across five detention facilities. Meditational analyses examined the relationship between personal strengths and burnout, through the construct of resilience. Results revealed hope, optimism, and social support are significantly associated with reduced burnout, and that this relationship is mediated by resilience. These results suggest that personal strengths can reduce burnout in correctional officers by increasing resilience. This is the first study to examine the effects of these positive psychology variables on burnout in a correctional officer population.